الاجتهاد المقاصدي: ضوابطه ومراتبه - شقوير، مجدي حسن أبو الفضل (جامعة الأزهر - كلية الشريعة والقانون بدمنهور, 2022)
يتناول هذا البحث الاجتهاد المقاصدي وهو مصطلح جديد لكن معناه وحقيقته موجودة وحاضرة بقوة في تراثنا الأصولي وقد مارسه الصحابة والتابعون والأئمة والعلماء، وقد تعرض هذا البحث لبيان معناه ووظيفته ووجه الاختلاف بينه وبين الاجتهاد الاصطلاحي المعروف عند الأصوليين، وقد بين هذا البحث أهمية أن يكون الاجتهاد المقاصدي منضبطا بضوابط محكمة تمنع أصحاب الأهواء من استغلاله في هدم أحكام الـشريعة والتفلت منها، وتعطيل النصوص الشرعية ولهذا فقد ذكر عددا من الضوابط التي وضعها العلماء للاجتهاد المقاصدي حتى يكون اجتهادا معتبرا عند العلماء، ثم تعرض البحث لبيان مراتب الاجتهاد المقاصدي الثلاث وأبرز دور المقاصد في هذه المراتب وهي مرتبة فهم النص الشرعي وتفسيره، ثم مرتنبة استنباط الحكم بناء على هذا الفهم للنص، ثم مرتبة تنزيل الحكم المستنبط وتطبيقه على الواقع والذي قد يؤدي إلى إلغاء تطبيق الحكم، أو تأجيل تطبيقه إلى حين زوال الظروف التي اقتضت ذلـك، أو استبدال هيئة الحكم بهيئة أخرى أشد أو أخف بحسب تحقيق المقصد منه. وقد خلص هذا البحث إلى ضرورة الانتباه إلى أهمية الاجتهاد المقاصدي ومنزلته وضرورة تفعيله إذ أن الاختلالات التشريعية والانحرافـات في الفتاوى والأحكـام التي تصدر عن غير المتخصصين مرجعها إغفال دور المقاصد في الاجتهاد. This research deals with intentional ijtihad, which is a new term, but its meaning and reality is present and strongly present in our fundamentalist heritage, and it was practiced by the Companions, followers, imams and scholars. It is disciplined with tight controls that prevent people of whims from exploiting it in demolishing the provisions of Sharia and evading them, and disrupting the legal texts. For this reason, he mentioned a number of controls that scholars have set for intentional ijtihad in order for it to be considered diligence considered by scholars. The ranks are the order of understanding and interpretation of the legal text, then the order of deriving the ruling based on this understanding of the text, then the order of downloading the deduced ruling and applying it to reality, which may lead to the abolition of the implementation of the ruling, or postponement of its application until the circumstances that necessitated that are removed, or the ruling body is replaced by a body Others are more severe or lighter according to the purpose of achieving it. This research concluded that it is harmful to pay attention to the importance and status of intentional ijtihad and the necessity of activating it, as the legislative imbalances and deviations in fatwas and rulings issued by non-specialists are due to the neglect of the role of objectives in ijtihad.
Keywords: الشريعة الإسلامية -- الاجتهاد الفقهي -- أصول الفقه -- الاجتهاد المقاصدي -- الأحكام الشرعية